Assessment of polybrominated diphenyl ethers and emerging brominated flame retardants in Pheretima (a Traditional Chinese Medicine): Occurrence, residue profiles, and potential health risks. (1st May 2021) - Sun, Jing; Hang, Taijun; Cao, Ling; Fan, Xialei; Feng, Youlong; Tan, Li; Li, Keyu; Wang, Qinyi; Liu, Yingxiang; Yang, Gongjun
Abstract: China produces and consumes large quantities of brominated flame retardants (BFRs) as well as several other unregulated electronic waste recycling activities, causing high BFR concentrations in the natural environment. Thus, Traditional Chinese Medicines (TCMs) may be contaminated by legacy BFRs (e.g. polybrominated diphenyl ethers (PBDEs)) and emerging BFRs (eBFRs, such as decabromodiphenyl ethane (DBDPE)) during growth, processing, packaging, and transportation. Pheretima, which is a typical animal drug recorded in Chinese Pharmacopoeia, was used as an example to evaluate human exposure to BFRs through TCM intake. This study is the first to determine 25 PBDEs and 5 eBFRs in Pheretima and estimate the daily BFR intake via Pheretima -containing TCMs. Twenty-seven Shanghai Pheretima and fifty-one Guang Pheretima samples were collected between March and June 2019 in southeast China. High BFR detection frequencies were found in Pheretima, of which BDE-209 and DBDPE were the most predominant analytes. The total PBDE contents ranged from 73 pg/g to 8, 725 pg/g, while that of the eBFRs varied between 115 pg/g and 2, 824 pg/g. The profiles and abundances were found to be species- and origin-dependent. However, the traditional processing of Pheretima may reduce BFR residues. Based on the usual clinical doses of Pheretima and the available chronic oral reference doses of BDE-47, 99, 153, and 209, the mean (95th percentile) of the total hazard quotient was estimated to be 9.1 × 10 −5 (2.7 × 10 −4 ). Therefore, there is little risk related to BFR exposure for patients taking formulated Pheretima -containing TCMs. However, it is necessary to establish routine monitoring programs for the co-existence of pollutants in TCMs to perform a systematic and comprehensive risk assessment. Graphical abstract: Image 1 Highlights: It is the first assessment of BFRs residues in Traditional Chinese Medicine (TCM). Both legacy PBDEs and eBFRs were extensively determined in Pheretima. BDE-209 and DBDPE were the predominant BFRs in all the samples. Shanghai Pheretima showed higher residues of BFRs than Guang Pheretima in general. No BFRs exposure related health risk was found via Pheretima -containing TCM intake. Abstract : The first assessment of PBDE and eBFR residues in Traditional Chinese Medicines.